Agua, sistemas de regadío y mito en el valle de Ica, 1900-1960 - Oré Vélez, María Teresa (1986)
The Peruvian coast is characterized by the presence of large desert areas, in the middle of which some valleys stand out as an exception. That is why the ancient existential pre-Hispanic hydraulic systems are particularly important to the extent that they allowed expanding the scarce water resources existing in the area. Thus, they enabled the emergence and development of the currently existing coastal agricultural valleys. Thus, various authors, including Macera, draw our attention to this aspect currently forgotten by researchers: understanding the development of coastal agriculture from recognizing it as hydraulic societies.